2014
DOI: 10.1021/ja4132246
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Enhancement of Perovskite Solar Cells through Fast Electron Extraction: The Role of Graphene Quantum Dots

Abstract: We report on a significant power conversion efficiency improvement of perovskite solar cells from 8.81% to 10.15% due to insertion of an ultrathin graphene quantum dots (GQDs) layer between perovskite and TiO2. A strong quenching of perovskite photoluminescence was observed at ∼760 nm upon the addition of the GQDs, which is pronouncedly correlated with the increase of the IPCE and the APCE of the respective cells. From the transient absorption measurements, the improved cell efficiency can be attributed to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
500
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 711 publications
(516 citation statements)
references
References 25 publications
14
500
1
1
Order By: Relevance
“…It should be noted that the previous studies have shown decreased and/or unchanged V oc values of PSC devices after the incorporation of various nanocarbon materials into the ETLs 39, 40, 42. Interestingly, our study demonstrates that the addition of a small amount of SWCNTs into the ETL leads to a considerable enhancement in the V oc .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It should be noted that the previous studies have shown decreased and/or unchanged V oc values of PSC devices after the incorporation of various nanocarbon materials into the ETLs 39, 40, 42. Interestingly, our study demonstrates that the addition of a small amount of SWCNTs into the ETL leads to a considerable enhancement in the V oc .…”
Section: Resultsmentioning
confidence: 83%
“…On the other hand, the incorporation of highly conductive carbon nanomaterials such as graphene and carbon nanotubes (CNTs) has also been proven to be an effective method to facilitate the charge transport and extend the electron lifetime, thereby enhancing the efficiency of PV devices 22, 34, 35, 36, 37. Although graphene and its derivatives have been successfully utilized for improving the performance of PSCs,38, 39, 40, 41, 42, 43 there has been no effort in the application of CNTs for use in PSC photoelectrodes. It should be noted that due to their unique structure and outstanding properties including excellent conductivity and high optical transparency, CNTs have exhibited promising results when they are used as an HTM and cathode in PSCs 44, 45, 46, 47, 48, 49.…”
Section: Introductionmentioning
confidence: 99%
“…Even so, the utilization of graphene film in perovskite SCs has been rarely explored up to now, therein graphene‐based films have been served as interlayers with success for high‐efficiency charge transfer or collecting 76, 77. Recently, Yan et al first reported the laminating stacked multilayer graphene serving as top electrode for semitransparent perovskite SC 78.…”
Section: The Human‐like Senses and Feedbacksmentioning
confidence: 99%
“…Besides, for PVSCs with the stratified configuration, it is important to control the appropriate electrical properties at each interface in the device in order to facilitate charge collection while minimizing the charge recombination 8. This necessitates the understanding of the electronic structure and energy level alignment at the metal electrode/charge‐transporting layer (CTL)/perovskite interfaces.…”
mentioning
confidence: 99%